I skuggan av kulturella stereotypier: perspektiv på forskning om genus, jämställdhet och etniska relationer i Sverige (Sociologisk Forskning, 2011)
In the shadow of ethno-cultural stereotypes: gender, equity and ethnic relations in SwedenScientific debates about cultural differences between ”Swedes” and migrants/ethnic minorities in Sweden have fuelled stereotypical categorizations and a socio-cultural demarcation between ”us” and ”them”. The authors argue that this development has underpinned constructions of foreignness. In the light of a critical review of the current debate on honour related violence, the authors discuss – inspired by Georg Simmel’s and Erving Goffman’s classic texts on the stranger, the stigma and the construction of foreignness – alternative understandings of culture and politics of belonging with a focus on gender, agency and identity formation. Formation of cultural and ethnic identity should be related, the authors conclude, to a dynamic interplay between the past and the present. Moreover, the social dimension should be highlighted, in order to avoid a stigmatizing culturalism.
Keywords: ethnicity; gender; gender equality; cultural analysis